Prediction of glaucoma from fundus images leveraging transfer learning in deep neural network - Ismail, Sayem Mohammad; Hossain, Md. Sajjad; Sobhan, Irina (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2020.